Evaluation of novel TGR5 agonist in combination with Sitagliptin for possible treatment of type 2 diabetes. Issue 10 (1st June 2018) - Agarwal, Sameer; Sasane, Santosh; Kumar, Jeevan; Deshmukh, Prashant; Bhayani, Hitesh; Giri, Poonam; Giri, Suresh; Soman, Shubhangi; Kulkarni, Neelima; Jain, Mukul
Graphical abstract: A series of novel 2-thio-imidazole derivatives have been identified as potent and orally efficacious TGR5 agonists. Compound 4d, a novel TGR5 agonist, in combination with Sitagliptin, a DPP-4 inhibitor, has demonstrated an adequate GLP-1 secretion and glucose lowering effect in animal models, suggesting a potential clinical option in treatment of type-2 diabetes. Highlights: Novel 2-thio-imidazole derivatives have been identified as potent TGR5 agonist. Compound 4d in combination with Sitagliptin, shows GLP-1 secretion in animal models. Combination of these agents shows glucose lowering effect in animal models. TGR5 agonist & DPP-4 inhibitor combination is a possible clinical option for treatment of type-2 diabetes. Abstract: TGR5 is a member of G protein-coupled receptor (GPCR) superfamily, a promising molecular target for metabolic diseases. Activation of TGR5 promotes secretion of glucagon-like peptide-1 (GLP-1), which activates insulin secretion. A series of 2-thio-imidazole derivatives have been identified as novel, potent and orally efficacious TGR5 agonists. Compound 4d, a novel TGR5 agonist, in combination with Sitagliptin, a DPP-4 inhibitor, has demonstrated an adequate GLP-1 secretion and glucose lowering effect in animal models, suggesting a potential clinical option in treatment of type-2 diabetes.